The Australian truffle industry: History, challenges and opportunities - Mahesh C.A. Galappaththi; Jen McComb; Sarah J. Sapsford; Giles E. St J. Hardy; Treena I. Burgess (Journal of Agriculture and Food Research)
Tuber melanosporum was first harvested in Australia in 1999, and exports began in 2007. Australia is now the world's fourth-largest truffle producer. The main challenges Australian producers face are climate change, obtaining well-mycorrhized seedlings with no contaminants, and preventing entry of the contaminant species T. indicum and T. maculatum to Australia and T. brumale from east to Western Australia. There is also increasing competition from other southern hemisphere countries. Almost all truffle orchards in Australia are in regions with 600–1500 mm annual rainfall and a mean daily mid-summer temperature below 25 °C. As soils in agricultural lands of Australia are frequently acidic, lime is applied to achieve the alkaline pH required by truffles. New truffle orchards should be planned bearing in mind future climatic predictions. The incorporation of more T. borchii and T. aestivum in truffieres, and the possible use of T. magnatum will spread the harvest period, and thus exports. Oaks and hazel are currently used as major hosts, and new host species are being investigated, including Pinus. The cost of establishing a truffiere in Australia is high. However, Australia lacks many pests, diseases, and social problems associated with the European industry, and together with being an environmentally friendly industry, these factors make truffle production an attractive agricultural investment in Australia which will aid regional economies.